An in vitro study to elucidate the effects of Septilin TM on immune pathways (Bangladesh Journal of Medical Science, 2018)
Objective: The use of herbal immunomodulatory preparations to prevent and treat immunological complications is increasing in popularity. Rigorous in vitro, in vivo and clinical trial studies are needed to ensure safety, quality and efficacy for the wellbeing of patients. SeptilinTM, a proprietary herbal medicinal product has been reported to have immunomodulatory effects. This study investigated the in vitro effects of SeptilinTM on biomarkers of specific immune pathways by using whole blood culture assays (WBC).Materials and Methods: Stimulated and unstimulated WBC have been incubated with the product. Enzyme linked immunosorbent assays have been used to screen for IL-6, IL-10, and IFN γ as biomarkers for inflammation, humoral immunity, and cell mediated immunity, respectively.Results: SeptilinTM had no effect on the release of IL-6 production by (lipopolysaccharide) LPS stimulated WBC across all concentrations tested. However, SeptilinTM induced significant higher levels (P